Heavy Metal of Lead (Pb) Profile in Water, Sediment and Seagrass (Thalassia hemprichii) in Ambon Island - Tupan, Charlotha I.; Herawati, E. Y.; Herawati, E. Y.; Arfiati, D.; Aulanni’am, Aulanni’am (Proceeding International Conference on Global Resource Conservation, 2013)
Differences in the accumulation of lead heavy metal among plant organs (leaves, roots and rhizomes) were examined in the seagrass Thalassia hemprichii. Samples were taken from three coastal waters in Ambon Island, with total of nine sampling sites encompassing by seagrass distribution and also based on the land use. Lead heavy metal content was analyzed on the seagrass organs, water and sediment by atomic absoption spectrophotometer. It appeared that leaves, roots and rhizomes of T. hemprichii were able to uptake lead from water and sediment. Lead concentration was significantly higher in sediment and roots than water, leave and rhizome. Therefore, roots can be used to determine heavy metal of Pb distribution in coastal waters.